Feasibility, acceptability, and design of a mobile health application for high-risk men who have sex with men in Hanoi, Vietnam - Kathy Trang, MA; Patrick S Sullivan, PhD; Devon E Hinton, MD; Carol M Worthman, PhD; Minh Giang Le, MD; Tanja Jovanovic, PhD (Elsevier, 2020)
Background: Approximately three quarters of men who have sex with men (MSM) in Vietnam have used a phone or tablet to search for sexual health information online, and over half of these men have used it to locate nearby service providers. As HIV prevalence continues to rise in Vietnamese MSM, smartphones and other electronic media may provide an ideal platform for HIV research and intervention. Here, we describe a pilot study of an ecological momentary assessment (EMA) application (app) and a wearable device (MC10 BioStamp) to monitor risk-taking behaviours and mental health symptomatology and assess the feasibility and acceptability of the app, and mobile health (mHealth) needs of MSM in Vietnam. Methods: We recruited 50 participants from outpatient clinics and community-based organisations for MSM in Hanoi, Vietnam. For 1 week, participants completed brief surveys on their smartphone at six to eight random time-points every day. At each time-point, participants answered questions assessing: current mood; stress level; qualities of their current environment (including who they were with); mental health symptoms since last notification; risk behaviours; and GPS location (automatically recorded). They additionally wore two sensors on their chest and thigh, monitoring ambulatory heart rate and physical activity. After the week, participants were interviewed about their experiences using the application and were asked survey questions about what features they wanted in future mHealth-related apps. Findings: Participants were identified from an existing dataset of MSM (n=198) and invited to return for the study between January and April 2019. Overall, participants reported few issues with the sensors; however, they had more concerns about the app. The most frequent complaints participants had were that the assessments were too repetitive, too frequent, and did not provide enough opportunity for in-depth qualitative responses. What participants most enjoyed about the app was that it provided an opportunity to share and to reflect on their moods and social interactions. To improve, participants felt the messaging needed to be more MSM-friendly and visually appealing, while providing occasional statistics on their weekly moods or behaviours. The most popular app features desired were the ability to talk directly to a service provider about ongoing health concerns (91%; 40/44), locate nearby PrEP providers (82%; 36/44), and locate a nearby HIV/STD testing centre (82%; 36/44). Interpretation: This study found that mobile EMA apps and wearable technology are a feasible and acceptable way of monitoring mental distress and HIV risk among MSM in Vietnam. Given that many were already looking towards the app as a means to self-manage and acquire more health-related information, mobile technologies may be a natural platform for bridging research and intervention among this population. Funding: PHRMA Foundation; Global Health Institute and Center for Culture, Mind, Brain at Emory University; Robert Lemelson Foundation, Society for Psychological Anthropology; Healthcare Innovation Program/Georgia CTSA; American Society of Tropical Medicine & Hygiene; Ben Kean Fellowship Committee.